Neuroprotective effect of epigallocatechin-3-gallate against N-methyl-D-aspartate-induced excitotoxicity in the adult rat retina - Chen, Fei; Jonas, Jost B. (Acta ophthalmologica, 2012)
Abstract. Purpose: Epigallocatechin-3-gallate (EGCG), the major polyphenol of green tea, has been suggested to reduce glutamate excitotoxicity. We therefore investigated the potentially protective effects of EGCG against N-methyl-d-aspartate (NMDA)-induced excitotoxicity in the retina. Methods: Female Wistar rats (n = 171) were divided into a normal control group (n = 9); saline control group with intravitreal saline injections (n = 54); NMDA control group with an intravitreal NMDA injection and intraperitoneal saline injections (n = 54); and NMDA study group (n = 54) receiving an intravitreal NMDA injection plus intraperitoneal EGCG (25 mg/kg) injections. Starting at 2 days prior to the intravitreal NMDA injection, the intraperitoneal injections were performed daily for the whole study period. At 12 hr, 1, 2, 3 days, 1 and 2 weeks after the intravitreal NMDA injection, the animals were killed. We counted the neurons in the retinal ganglion cell layer (GCL) on histological sections, measured the thickness of Thy-1 immunoreactivity and assessed the expression of Thy-1 mRNA by real-time polymerase chain reaction. Results: At all time-points, GCL cell density, thickness of Thy-1 immunoreactivity and expression of Thy-1 mRNA were significantly (all p < 0.05) lower in the NMDA control group than in the NMDA study group, in which the parameters were significantly (all p < 0.05) lower than in the saline control group and the normal control group. In both groups with an intravitreal NMDA injection, GCL cell density, thickness of Thy-1 immunoreactivity and expression of Thy-1 mRNA decreased significantly with increasing follow-up time. Conclusions: Intraperitoneal application of EGCG resulted in a significantly less marked NMDA-associated loss of retinal ganglion cells.
First published: 13 September 2012
Gesehen am 26.06.2018